Matematyka
kris4991
2017-06-23 23:31:59
Przyjmując, że log9=a i log6=b zapisz podane logarytmy przy pomaocy a i b a)log24 b)log16 c)log1,5 d)log[latex]3 sqrt{2} [/latex] 3)log[latex]1 frac{1}{2} [/latex]
Odpowiedź
jaaaaaaaaaaa
2017-06-24 02:51:47

[latex]a=log9=log3^2=2log3Rightarrow log3=frac{a}{2}\log6-log3=b-frac{a}{2}=logfrac{6}{3}=log2\log2=logsqrt{2}^2=2logsqrt{2}Rightarrow logsqrt{2}=frac{log2}{2}=frac{b}{2}-frac{a}{4}[/latex] Otrzymujemy: [latex]log2=b-frac{a}{2}\log3=frac{a}{2}\logsqrt2=frac{b}{2}-frac{a}{4}\log24=log(2cdot2cdot2cdot3)=log2+log2+log2+log3=\=b-frac{a}{2}+b-frac{a}{2}+b-frac{a}{2}+frac{a}{2}=oxed{3b-a}\log16=log(2cdot2cdot2cdot2)=log2+log2+log2+log2=\=b-frac{a}{2}+b-frac{a}{2}+b-frac{a}{2}+b-frac{a}{2}=oxed{4b-2a}\log1,5=log(frac{3}{2})=log3-log2=frac{a}{2}-(b-frac{a}{2})=frac{a}{2}-b+frac{a}{2}=oxed{a-b}[/latex] [latex]log3sqrt2=log(3cdotsqrt2)=log3+logsqrt2=frac{a}{2}+frac{b}{2}-frac{a}{4}=oxed{frac{a}{4}+frac{b}{2}}\log1frac{1}{2}=log1,5=oxed{a-b}[/latex]

Dodaj swoją odpowiedź